EFEK MODERASI PATRIOTISME ATAS PEMAHAMAN PERATURAN PERPAJAKAN, PELAYANAN PUBLIK DAN PERKEMBANGAN INFORMASI PADA KEPATUHAN WAJIB PAJAK - Mishelei Loen; Ramadhan Hasri Harahap (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This study aims to determine the Understanding of Tax Regulations, Public Services, and Information Development on Taxpayer Compliance moderated by Patriotism. This research was conducted with a quantitative approach with a survey method. The population in this study were taxpayers registered at the cooperative office and as many as 160 respondents with sampling determination, namely purposive sampling. The analysis technique used in this research is SEM through the PLS application. The results of this study indicate that understanding tax regulations, public services, and information development affect taxpayer compliance. Patriotism moderates tax regulations and public services on taxpayer compliance. Meanwhile, information development on taxpayer compliance is not moderated by patriotism. This research is expected to provide a benefit for the government to further socialize information about taxes through brochures, mass media or providing brochures from house to house. And for tax officials to provide better service and provide examples, so that taxpayers can accept positively towards tax officials so that the level of compliance in carrying out tax obligations increases